Self-perceptions of Airbnb hosts’ responsibility: a moral identity perspective - Farmaki, Anna; Stergiou, Dimitrios P.; Kaniadakis, Antonios (My University, 2019)
Responsible host conduct has emerged as important in regulating the peer-to-peer accommodation phenomenon. Utilising moral identity theory, this paper explores how hosts draw on their own perceptions of morality and responsibility to inform hosting practice. Through a qualitative research approach, the study reveals a variance of host practices that are not necessarily reflective of the perceived moral identity of hosts. In particular, the paper exposes the moral questions that hosts need to answer at different phases of the peer-to-peer transaction and, especially, if and how they enact certain aspects of their moral identity to guide their behaviour. The study offers a typology of Airbnb hosts’ (im)moral behaviour, which may be of theoretical and practical value to academics and policymakers alike.
Keywords: Moral identity; Responsibility; Host perceptions; Airbnb